Pengaruh Profitabilitas dan Kesempatan Investasi terhadap Kebijakan Deviden melalui Likuiditas sebagai Variabel Moderasi - Widyawati, Rika (Al-Muhasib: Journal of Islamic Accounting and Finance, 2021)
This study aims to determine the direct effect of profitability and investment opportunity set toward dividend policy and the indirect effect of profitability and investment opportunity set toward dividend policy through liquidity as moderating variable. This research is explanatory. The data collection was done by using documentation in the form of annual financial statements at a registered company listed on the index Kompas 100 period 2010-2012. This study uses path analysis. The results of hypothesis testing showed that: (1) Profitability had no effect on dividend policy, (2) Profitability had a positive effect on dividend policy through liquidity as moderating variable, and (3) Investment opportunity set had no effect on dividend policy, (4) Investment opportunity set had a positive effect on dividend policy through liquidity as moderating variable. This study has limitations in that the company who search had good liquidity, good fundamentals, and finances so the company pays high dividends although had low profitability. Therefore, further studies are expected to be able to add other variables that may affect the dividend policy